Novel Histone Deacetylase Inhibitors for the Treatment of Pediatric Brain Tumors - V. de Andrade, Pamela; F. Andrade, Augusto; G. de Paula Queiroz, Rosane; A. Trevisan, Felipe; G. Tone, Luiz; T. Valera, Elvis (Central Nervous System Agents in Medicinal Chemistry, 2014)
Pediatric brain tumors (BT) represent a broad group of malignancies that affect children, displaying different degrees of aggressiveness and prognosis. Current studies demonstrate a crosslink between genetic and epigenetic changes within these tumors. Histone modifications are key elements in the pathogenesis of cancer in general and in brain tumors in particular. It is well documented that at least two classes of enzymes control acetylation of histones: histone acetyltransferases (HATs) and histone deacetylase (HDACs). Transformed HAT or HDAC action was identified in a number of human tumors. It has been hypothesized that HDACs regulate gene expression by deacetylating important genes for cell maintenance. Several HDACs inhibitors have been characterized in the last years and have been shown to promote growth blockage, differentiation and apoptosis in various types of tumors, including glioblastomas, medulloblastomas, neuroblastomas, melanomas, and leukemias. Some of these inhibitors are currently under clinical investigation for different cancer treatments. This review summarizes important mechanisms of histone modifications and discusses recent discoveries with impact on the pre-clinical and clinical field of pediatric brain tumor treatment.
Keywords: histone deacetylase inhibitors